Development of shear stress equation contributed by steel fibre in reinforced concrete - Sarbini, N. N. (Asian Research Publishing Network, 2016)
The rise of extensive research and development on the application of steel fibre inside concrete is a tremendous topic in the last few decades. The obvious benefits of adding steel fibre inside concrete can be seen from the improvement of the mechanical properties of steel fibre reinforced concrete (SFRC). The improvement of the mechanical properties can be seen easily on the higher value of tensile and flexural strengths for SFRC compared to plain concrete. However, a question arises on to what extent does the steel fibre exerts an additional stress to increase the strength. Currently, this additional stress is called "shear stress supplement". In this study, shear supplement model developed by Rilem was quantified with some statistical modification to predict the additional shear exerted by the steel fibre when it is placed inside the concrete. To achieve the objective, 51 prism specimens (150 mm × 150 mm × 750 mm) were prepared and differ in terms of the type of steel fibre and the fibre volume fraction, Vf. Two types of hooked-end steel fibre labeled as SF60 and SF50 were used in this research. Meanwhile, each type of steel fibre was mixed into a plain concrete with respect to the Vf of 0.25%, 0.50%, 0.75%, 1.00%, 1.25%, 1.50%, 1.75%, and 2.00%. Plain concrete prisms were prepared as the control specimens. After 28 days of curing period, the prism was then transferred to the test frame to undergo flexural strength test. The results from the flexural strength test were used to develop the shear stress equation to predict the contribution of steel fibre to increase the shear stress. The modified equation was then used to predict the value of shear stress supplement. The results showed that, the modified model well predicted the shear stress supplied by the steel fibres well which was shown by higher coefficient of correlation.